Liver transplantation for acute liver failure following leprosy treatment: Case report - Melo, Paulo Sérgio Vieira de (2019)
The incidence of drug-induced acute liver failure has increased. Among the drugs involved are especially antibiotics such as rifampicin and dapsone involved in the treatment of leprosy. Dapsone hypersensitivity syndrome (DHS) is a rare adverse reaction. This syndrome is characterized by fever, exfoliative dermatitis, lymphadenopathy, anemia and liver involvement, which includes hepatocyte necrosis and cholestasis. Acute liver failure due to DHS may be an indication for emergency liver transplantation, a rarely reported condition in the literature. For the present study, the patient’s pre and postoperative data were analyzed through his medical record. A non-systematic search was conducted by using PubMed and Scielo database to find the most up-to-date literature on drug-induced acute liver failure and DHS. A 23-year-old male patient was admitted to a referral center after undergoing combined therapy for Virchowian leprosy (dapsone, rifampicin, clofazimine) for approximately 30 days. The patient presented severe progressive jaundice, anemia, coagulopathy and grade IV encephalopathy (West-Haven criteria) in addition to elevated liver enzymes and acute kidney injury. The patient was enlisted for liver transplantation with 40 MELD score (model for end-stage liver disease). The surgical technique employed was piggyback using a deceased donor allograft (donation after brain death). The post-transplant clinical improvement was substantial. Histopathological assessment of the native liver showed compatibility with drug-induced acute hepatitis. Although rarely indicated in cases of acute hepatitis associated to DHS, liver transplantation has been shown to be effective in this context, improving the prognosis of otherwise terminal patients. The present case should alert for the need of clinical and biochemical monitoring of patients undergoing treatment for leprosy. Patients and professionals should also be informed on DHS signs and symptoms, in view of its potentially fatal repercussions.